Mean Circumferential Fibers Shortening Velocity Assessment in Patients with type II Diabetes Mellitus in relation to their Diastolic Function Status - Asaad Hasan Noaman1 , Amina A. B. Al-Dejeli2 and Falah Mahdi Dananah (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The most important cause of death in diabetic patients is the cardiac insult. Mean circumferentialfibers shortening velocity (MCFSV) was used to detect the systolic cardiac dysfunction.Objective: This study aimed to evaluate MCFSV in people who have Type 2 diabetes.Patients and methods: This analytic observational study was performed in Al-Furat teaching hospital.Eighty type 2 diabetics were involved in this study. All patients were subjected to traditional Dopplermeasures: tissue Doppler-derived E/E,and MCFSV.Results: Echocardiographic measures revealed 35 subjects having Grade I of Diastolic dysfunction (DD), 15having Grade II while 10 were diagnosed with Grade III of this condition. MCFSV did not change in patientswith normal diastolic function (0.00137±2.02) and those with grade I diastolic dysfunction (0.00148±3.5),(P value: 0.2) while significant reduction was documented in patients with grade II diastolic dysfunction(0.0011±9.1, P value: 0.00) and grade III diastolic dysfunction (0.001±6.02, P value: 0.00)Conclusions: There is a connection between Reduction of MCFSV and increased grading of diastolicdysfunction (DD) in type II diabetics.